Creative-Innovative Role and Human Capital: An Interrelationship Analysis - Ridho, Sari Lestari Zainal; Miskiyah, Neneng (Universitas Muhammadiyah Yogyakarta, 2020)
Improving performance as an effort to deal with change is a necessity, so the use of digital marketing to improve organizational performance in developing the tourism industry in Indonesia in the industrial era 4.0, applied to the Indonesian Ministry of Tourism, one of which is in the implementation of the Indonesian Enchantment Generation. The purpose of this study is to clarify the impact of human, social and intellectual capital from the use of digital marketing on the creative and improvise role of the Indonesian Enchantment Generation members. This research uses a survey approach. The study population was members of the tourism community, the Ministry of Tourism in Indonesia, selected as a sample in this study. Hypothetically, it is believed that human, social and organizational capital has a linear and positive relationship to the creative and innovative roles of community members, and this study will present the results of data processing of relationships between these variables, which are processed using regression techniques. Based on the results of the study, it can be concluded that human capital and intellectual capital have a positive and significant influence on the creative and innovative role of the Indonesian Enchantment Generation community members in Indonesia.